적색 국화의 화색발현에 있어 고온에 민감한 생육 단계와 품종별 고온적응성 비교 - 허은주(Eun Joo Huh); 신학기(Hak Ki Shin); 최성렬(Seong Youl Choi); 권오근(Oh Geun Kwon); 이영란(Young Ran Lee) (Weon'ye gwahag gi'sulji, 2008)
국화의 화색발현에 있어 고온에 민감한 화아발달단계를 구명하고자 국화의 화아 발달 과정을 4단계로 나누어 고온 처리하였다. 그 결과 꽃봉오리가 터지는 시기에 고온에 접하였을 때 안토시아닌 함량이 가장 많이 감소되어 ‘Relance’의 경우 35/20℃ 처리시 안토시아닌 함량이 25/20℃ 처리구의 48% 수준으로 감소하였다. 고온에 대한 화색의 반응은 ‘Relance’와 ‘Wembley’에서 다소 다르게 나타났다. ‘Relance’의 안토시아닌 함량은 35/20℃에 접할 경우 25/20℃에 비해 약 43.4% 감소한 반면 ‘Wembley’는 약 10% 정도만 감소하여 고온의 영향을 적게 받는 것으로 나타났다. 안토시아닌 생합성 유전자의 발현을 분석한 결과 dihydroflavonol reductase (DFR)와 anthocyanin synthase(ANS)는 두 품종 모두에서 고온에 의해 발현이 현저히 감소하였다. 그러나 고온에 의한 flavanone 3-hydoxylase(F3H)의 발현의 감소 정도는 ‘Wembley’ 품종에서 다소 적게 나타났다. The study showed that among the four different flower developmental stages, anthocyanin content was extremely decreased by high temperature when plants were exposed at bud opening stage for seven days. During that stage, anthocyanin content of ‘Relance’ flowers subjected to 35/20℃ was about 48% that of flowers exposed to 25/20℃. On the other hand, the color response to high temperature differed between two red chrysanthemum cultivars, ‘Relance’ and ‘Wembley’. Anthocyanin content of ‘Relance’ was reduced by 43.4% at high temperature (35/20℃) when compared with those exposed to 25/20℃. However, that of ‘Wembley’, which was less affected by temperature, resulted in only 10% reduction at 35/20℃. The gene transcripts, especially dihydroflavonol reductase (DFR) and anthocyanin synthase (ANS), were reduced extremely by high temperature in both cultivars. Reduction in flavanone 3-hydoxylase (F3H) expression by high temperature was less in ‘Wembley’ than in ‘Relance’. KCI Citation Count: 13